Targeting matrix metalloproteinase-9 (MMP9) in prostate cancer: a computational study on natural product-derived novel potential inhibitors - Vipendra Kumar Singh; Naina Rajak; Prashant Kumar Gupta; Arun Kumar Mahapatra; Ankit Kumar Singh; Rajanish Giri; Neha Garg (Future Journal of Pharmaceutical Sciences)
Abstract Background Prostate cancer is one of the prime causes of death in men worldwide; the number of patients has increased every year despite significant efforts and outlay in the research of prostate cancer. Identifying new natural targets for effective prostate cancer treatment remains a major challenge in contemporary research. Natural products may provide an excellent source for drug development against prostate cancer. The DisGeNET and GeneCards databases were used to identify the anti-cancer proteins involved in prostate cancer. Furthermore, the Search Tool for the Retrieval of Interacting Genes/Proteins database was utilized to identify the hub genes. The hub genes were processed using the Gene Expression Profiling Interactive Analysis database to get the difference in transcriptional expression between prostate cancer tissue and normal tissue. The 3D structures of selected targets were acquired from the protein data bank, and molecular docking was carried out. Higher expression of hub genes such as matrix metalloproteinase-9 (MMP9) was significantly linked with overall and progression-free survival in prostate cancer patients. Finally, the 200 ns molecular dynamics (MD) simulation was performed to check the stable interaction of compounds with the MMP9. Results Co-expression investigation demonstrates that identified hub genes play a crucial role in prostate cancer and are controlled by many miRNAs. Molecular docking studies demonstrated that D-Galacturonic acid, glycerides, C14-18 showed better docking scores (− 8.0) with targeted MMP9 protein. MD simulation showed a stable interaction of bioactive compounds, such as D-Galacturonic acid, glycerides, C14-18 with the MMP9 protein. Conclusions The present study highlights that bioactive compounds could be an effective anti-cancer drug against MMP9 in prostate cancer and can be further validated using different preclinical studies. Graphical abstract